Carbon Dioxide Emissions along the Lower Amazon River - Sawakuchi, Henrique O.; Neu, Vania; Ward, Nicholas D.; Barros, Maria de Lourdes C.; Valerio, Aline M.; Gagne-Maynard, William; Cunha, Alan C.; Less, Diani F. S.; Diniz, Joel E. M.; Brito, Daimio C.; Krusche, Alex V.; Richey, Jeffrey E. (Frontiers in Marine Science, 2017)
A large fraction of the organic carbon derived from land that is transported through inland waters is decomposed along river systems and emitted to the atmosphere as carbon dioxide (CO2). The Amazon River outgasses nearly as much CO2 as the rainforest sequesters on an annual basis, representing ~25% of global CO2 emissions from inland waters. However, current estimates of CO2 outgassing from the Amazon basin are based on a conservative upscaling of measurements made in the central Amazon, meaning both basin and global scale budgets are likely underestimated. The lower Amazon River, from Óbidos to the river mouth, represents ~13% of the total drainage basin area, and is not included in current basin-scale estimates. Here, we assessed the concentration and evasion rate of CO2 along the lower Amazon River corridor and its major tributaries, the Tapajós and Xingu Rivers. Evasive CO2 fluxes were directly measured using floating chambers and gas transfer coefficients (k600) were calculated for different hydrological seasons. Temporal variations in pCO2 and CO2 emissions were similar to previous observations throughout the Amazon (e.g. peak concentrations at high water) and CO2 outgassing was lower in the clearwater tributaries compared to the mainstem. However, k600 values were higher than previously reported upstream likely due to the generally windier conditions, turbulence caused by tidal forces, and an amplification of these factors in the wider channels with a longer fetch. We estimate that the lower Amazon River mainstem emits 0.2 Pg C yr-1 within our study boundaries, or as much as 0.48 Pg C yr-1 if the entire spatial extent to the geographical mouth is considered. Including these values with updated basin scale estimates and estimates of CO2 outgassing from small streams we estimate that the Amazon running waters outgasses as much as 1.39 Pg C yr-1, increasing the global emissions from inland waters by 43% for a total of 2.9 Pg C yr-1. These results highlight a large missing gap in basin-scale carbon budgets along the complete continuum of the Amazon River, and likely most other large river systems, that could drastically alter global scale carbon budgets.